Indonesian EFL Undergraduate Students’ Perceptions of English Critical Reading - Azhipa, Dinda Putri; Daflizar, Daflizar; Musdizal, Musdizal (Universitas Pahlawan Tuanku Tambusai, 2026)
Critical reading (CR) is a crucial academic literacy skill for English as a Foreign Language (EFL) students to evaluate and engage with academic texts. This mixed-method study explored Indonesian EFL students’ perceptions of critical reading, including their self-assessed CR skills, perceived institutional support, gender differences, and frequently read English reading materials. Quantitative data were collected from 100 students through questionnaires, followed by interviews with 10 participants. Results showed that students had positive perceptions of critical reading and recognized the importance of this skill in an academic context. However, advanced skills such as identifying bias and evaluating arguments remain challenging. The study found that gender was not a significant factor. Qualitative findings revealed linguistic difficulties and limited institutional support, even though students frequently interact with academic texts. Practical implications for teachers and educational institutions in the Indonesian context are put forward.